Analysis of indoor radon concentration levels and trends in China - Ding, Bowei; Wu, Yunyun; Song, Yanchao; Hou, Changsong; Shang, Bing (Frontiers in Public Health, 2025)
A systematic review of publicly available papers on indoor radon data from 1980 to 2023 was conducted to provide a preliminary understanding of indoor radon concentration levels and trends in China. Keywords were used to collect literature on indoor radon surveys in China during the periods of before 2000, 2000–2010 and after 2010 in the CNKI, WANFANG, VIP and PubMed databases. This paper also collected indoor radon concentration data from WHO, UNSCEAR publications and PubMed databases for other countries. A total of 37,886 indoor radon concentration data points were collected in China, covering 31 provinces. The results showed that the weighted and arithmetic mean radon concentrations in China were 29.4 Bq/m3 and 33.2 Bq/m3 (n = 17,940) before 2000, 44.7 Bq/m3 and 43.3 Bq/m3 (n = 10,692) in 2000–2010, 57.6 Bq/m3 and 60.8 Bq/m3(n = 9,254) after 2010, respectively. It indicated an increasing trend in indoor radon concentrations in China. The differences in mean indoor radon concentrations across time periods were significant (p < 0.001). In the regional analysis, the differences in indoor radon concentrations between different administrative geographic regions for each time period were significant (p < 0.05). Furthermore, the differences in indoor radon concentrations among climatic areas were significant for the periods 2000–2010 and after 2010 (p < 0.05). Additionally, this paper collected indoor radon data from 63 countries worldwide. The mean radon concentrations across the three periods—before 2000, 2000–2010 and after 2010—were 56.5 Bq/m3, 67.9 Bq/m3 and 81 Bq/m3, respectively. Meanwhile, a comparison of indoor radon concentration was made before and after 2000 among 26 countries, of which 16 countries showed an increasing trend. So, it can be seen the increase in indoor radon concentration in China is not an isolated phenomenon, and the issue of indoor radon pollution still requires further attention.